Solution Phase Deposition of Thin Films on Conversion Anodes for Lithium-Ion Batteries
By using solution phase technology to deposit flexible organic or mixed organic-inorganic materials on the surface of the conversion anode of lithium-ion batteries, the problems of stress and SEI instability during lithiation are solved, and the energy density and cycle life of the battery are improved. Reduces costs and improves security.
Patent Information
- Application Number
- CN202080031198.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-25
- Filing Date
- 2020-02-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-02-25
AI Technical Summary
The stress caused by volume expansion of the conversion anode material in existing lithium-ion batteries leads to crushing and electrical contact losses during the lithiation process, and the instability of the solid-electrolyte interface layer (SEI) leads to lithium ion consumption and capacity loss, limiting the battery cycle life.
Using solution phase technology to deposit flexible or mixed organic-inorganic materials as artificial SEIs on the conversion anode surface of lithium-ion batteries, through chemical bath deposition (CBD), layer-by-layer ion layer adsorption and reaction (SILAR) or layer-by-layer sol-gel The technology forms a mechanically robust, electrically insulated and lithium permeable film coating.
It improves the energy density and cycle life of lithium-ion batteries, reduces the formation of lithium-metal dendrites, reduces the cost of batteries, and improves safety. It is suitable for applications such as electric vehicles.
Smart Images

Figure CN114072948B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application No. 62 / 810,340, filed on February 25, 2019, which is incorporated herein by reference for all purposes. Technical Field
[0003] Embodiments of the present disclosure generally relate to various materials that, when grown on the surface of conversion electrodes (eg, lithium-ion battery conversion anodes) by solution phase deposition techniques, passivate their surfaces, preventing degradative reactions during operation. Background Art
[0004] Lithium-ion batteries (LIBs) are limited in energy density by the theoretical maximum capacity of the constituent materials comprising their anodes and cathodes. Graphite (the most common anode material in prior art LIBs) is an insertion electrode, in which lithium occupies the interplanar gaps between atomic graphene sheets when the battery is charged. Graphite does not undergo phase change during lithium insertion, but maintains the form of stacked planar sheets, although with strained interplanar van der Waals bonds compared to pre-lithiation. The limited space in which lithium ions are present in these interplanar gaps results in a moderate theoretical maximum specific capacity of graphite of about 372 mAh / g. The maximum Li to C atomic ratio observed in the inserted graphite is about 0.17:1. However, other materials (such as "alloying" or "conversion" materials) have significantly higher specific capacities than graphite, due to the fact that they undergo phase change during lithiation, enabling the lattice to be reconstructed into a new crystal structure of lithium with a significantly higher atomic fraction. For example, in the case of lithiated Si, it is observed that the atomic ratio of Li to Si exceeds 25 times that of fully lithiated graphite.
[0005] However, accommodating a large atomic fraction of lithium in an alloyed or converted material is generally accompanied by a large volume expansion of the host lattice. Alloying materials, which are a subset of conversion materials, include metals or semimetals such as Si, Ge, and Sn, which experience volume changes of 270%, 240%, and 255% when lithiated to voltages of 0.05, 0.2, and 0.4 V, respectively. Such volume expansion may induce stresses that exceed the fracture limit of the host material, leading to pulverization and subsequent loss of electrical contact with the underlying current collector.
[0006] Recent literature has proposed comminuting certain conversion and alloying lithium ion anode materials by reducing the particle size of the active materials of the lithium ion anode materials to the nanoscale. Many references indicate that nanostructured high capacity conversion and alloying anode materials can withstand large lithiation and delithiation strains without breaking. However, despite this progress, such materials still demonstrate large capacity losses when combined with standard prior art cathodes and cycled as full batteries. Subsequent studies of the surfaces of such nanostructured anode materials after cycling indicate that the main cause of capacity loss is not due to active particle rupture, but rather to an unstable interface layer between the active particles and the adjacent electrolyte, commonly referred to as a solid-electrolyte-interface or "SEI".
[0007] Specifically, the large volume expansion of the conversion anode during charging leads to three key failure mechanisms: (1) pulverization of the conversion anode active material due to internal stress during the charge / discharge cycle, (2) loss of adhesion and electronic conductivity between the conversion anode particles and the conductive binder or other active materials, and (3) consumption of lithium due to continuous regeneration of the surface passivation layer (SEI).
[0008] The SEI is a thin interfacial layer that forms on the surface of all lithium-ion battery anodes when the electrode potential is below the reduction stability limit of the adjacent electrolyte relative to some reference potential. For example, in a system comprising a graphite anode with an adjacent cyclic carbonate electrolyte (such as ethylene carbonate), the SEI is a thin interfacial layer that forms on the surface of all lithium-ion battery anodes when the electrode potential is below about 1 V relative to Li + / Li 0 The SEI begins to form when the electrolyte molecules are oxidized. In this case, the growth of the SEI is caused by the reduction of electrolyte molecules (ring opening in the case of ethylene carbonate), producing ionized species, which then combine with available lithium ions to precipitate solid insoluble lithium-organic compounds on the surface of the anode. The growth of this material is ultimately self-limiting because the molecules comprising the SEI tend to be electrically insulating and therefore hinder the transfer of electrons from the electrolyte to the electrode required for continuous electrolyte reduction. For example, in the case of prior art LIBs constructed with graphite anodes, the formation of this self-limiting SEI is crucial to the cyclability of the battery. A non-self-terminating SEI will inevitably consume all available lithium and severely limit the cycle life of the battery.
[0009] In the case of graphite anode, when close to full charge, the volume expansion of the host lattice is only about 10%. Therefore, any SEI present on the surface of the graphite anode also only needs to experience quite small tangential strain during this expansion. However, for alloying materials (such as Si, Ge or Sn), the volume expansion of >200% leads to the tangential strain of the fracture limit of the corresponding SEI layer of these materials. Similar volume expansion and unstable SEI are observed in other conversion materials (such as SnO2). As a result, the highly active field of research is to add new molecules to the electrolyte to form a more flexible SEI on the surface of alloying or converting anode materials. However, to date, it is not known that electrolyte additives can successfully make the cycle life of conversion or alloying anode materials close to the cycle life of prior art graphite.
[0010] Recent literature has demonstrated the use of oxides (e.g., Al2O3 grown by atomic layer deposition (ALD)) as SEI replacements (also called "artificial SEIs") in both graphite and conversion anodes. ALD can be performed on the anode powder either before or after electrode formation. Unfortunately, the necessarily high resistivity of the oxide artificial SEI produces considerable internal resistance when applied directly to the anode powder, which impedes proper operation of the cell. Therefore, the artificial SEI is best applied on a fully formed electrode, ideally using a deposition method that can be integrated into a typical roll-to-roll LIB manufacturing process.
[0011] However, roll-to-roll ALD has not yet proven to be a commercially viable process. The requirements for high deposition zone vacuum, high source and substrate temperatures to prevent precursor condensation, and the limited choice of precursors for deposition of organic and mixed organic-inorganic materials make roll-to-roll ALD impractical for implementation in high-volume, state-of-the-art LIB manufacturing. Therefore, there is a need to apply an artificial SEI to the surface of the alloying and conversion anode using a technique that is more feasible to introduce into the LIB manufacturing process than roll-to-roll ALD. Summary of the invention
[0012] In one aspect, the systems and methods of the present disclosure describe a solution phase technique for depositing novel materials (in the form of artificial SEI) on the surface of alloying and conversion electrodes (e.g., anodes). Compared to roll-to-roll ALD or other high vacuum vapor deposition methods, the methods disclosed herein are more commercially and technically feasible for introduction into high capacity lithium ion battery (LIB) manufacturing.
[0013] Nanoscale particles of alloying and conversion anode materials are usually synthesized to be roughly spherical in nature, because this minimizes the surface area to volume ratio, thereby maximizing capacity, while minimizing the losses caused by continuous SEI failure during cycling. If the volume expansion of the spherical particles of a specific conversion or alloying material is set to an approximate upper limit of, for example, 300% during lithiation, the corresponding surface area expansion will be roughly twice the original. Due to the above expansion, the mechanical strain experienced by any "artificial SEI" intentionally deposited on the surface of such particles will be roughly 100%. When considering the elongation at break of different types of candidate materials, almost no pure inorganic material exceeds 100%.
[0014] As a result, the present disclosure also focuses on the use of flexible organic or hybrid organic-inorganic materials with low elastic modulus, low hardness and high elongation at break as coatings on electrodes made from conversion or alloying materials. In addition, the present disclosure describes the production of high energy density LIBs consisting of anodes containing conversion materials by solving the problems associated with SEI formation, while also meeting industry standard cycle life requirements.
[0015] For decades, high-quality conformal thin films of inorganic materials have been deposited by solution phase techniques such as chemical bath deposition (CBD), successive ion layer adsorption and reaction (SILAR), and layer-by-layer sol-gel. In the CBD technique, an aqueous solution of a complexed metal precursor is (usually) mixed with a chalcogenide or oxide ion source. As is well known, CBD is used to deposit high-quality CdS or ZnS as n-type junction ligands on CdTe or CIGS thin film solar cells. The technique has been used for many years to set world record efficiencies for these types of solar cells. They produce high open circuit voltages, high diode idealities, and high shunt resistances, indicating excellent film quality and conformality. The CBD method has also been commercialized into high-volume thin film solar cell production lines.
[0016] A useful variation of the CBD technique is SILAR. In this case, the substrate is alternately exposed to cationic and anionic reactant solutions with a rinsing step in between. Although this technique results in slower film growth, the benefit of this technique is that homogeneous nucleation (precipitation) is eliminated from the mixing of the two reactants, which significantly improves material utilization. Considering the fact that the tunneling limit of a good dielectric is on the order of 1-2 nm, the SILAR technique is feasible for depositing a passivation layer on the surface of a battery electrode. The thickness control in the SILAR method is also better than that in the CBD method; for example, the thickness control of the passivation layer on the battery electrode is critical for preventing an undesirable barrier to lithium diffusion while maintaining an electron tunneling barrier.
[0017] There are also solution-based techniques that demonstrate layer-by-layer sol-gel coating using the same kinds of metal organics used in gas phase ALD. For example, a monolayer of Al2O3 can be grown by immersing the substrate in a solution of aluminum tri-sec-butoxide. Adsorption of the metal organic precursor followed by an oxidation step (e.g., hydrolysis) can produce a monolayer of the oxide. These steps are repeated with rinsing steps in between to obtain a monolayer-by-monolayer coating. Metal alkoxide precursors are typically soluble to very high molar concentrations in standard organic solvents such as 2-propanol.
[0018] In recent years, high-quality Al2O3, SiO2 and ZrO2 composite barrier layers have been grown on TiO2 dye-sensitized solar cells using this technique. As an example, ALD Al2O3 has recently been studied as an artificial SEI on silicon that converts anode materials. In the first few cycles, Al2O3 is converted to a glass electrolyte LiAlO2, resulting in a lithium-permeable surface layer that is still resistive. However, oxides (as typical SEIs) have high elastic moduli and low tensile strain limits. Therefore, such materials may also suffer from the same kind of brittle failure observed in SEIs of bare Si-. Finally, by completely encapsulating the particles in an insulating layer, the electrical pathways between the particles are effectively blocked, resulting in a substantial increase in internal resistance. The increased resistance by the sealant on the Si powder can be used to prevent SEI formation, but they prevent high-rate charging and high-peak discharge. In contrast, the technology disclosed in the present invention represents a high-throughput, low-cost, vacuum-free alternative to ALD that can be performed on formed electrodes rather than on particles, using mechanically flexible candidate coating materials.
[0019] A variation of gas phase ALD is gas phase molecular layer deposition (MLD). In gas phase MLD, molecular precursors with specific end groups react with functionalized surfaces in a self-limiting manner similar to ALD. However, the MLD reaction can be used to deposit a monolayer consisting of substantially larger molecules, rather than leaving an attached portion that is only one atomic monolayer thick. As an example, in the MLD growth of "Alucone", TMA is used as a metal organic precursor to provide an atomic monolayer of Al. Ethylene glycol is then used as an oxidant (as opposed to water or oxygen plasma in the ALD of Al2O3) and provides a 2-unit carbon chain attached to each deposited Al atom. Alternating deposition cycles of TMA and ethylene glycol (separated by a purge step) then provide a mixed organic material "alucone", which is significantly less dense and similar to other "metal cones" (such as silicone) than the corresponding oxide (Al2O3) grown by ALD. Alucone is an example of a mixed organic-inorganic material that can be deposited by MLD; organic polymers (such as polyamides) can also theoretically be deposited by MLD. Such materials are also known to have higher mechanical flexibility than purely inorganic materials typically grown by ALD, and may therefore serve as better candidates for artificial SEIs on conversion anodes produced by the methods and systems described herein.
[0020] As with ALD, there is also a solution phase analogous to gas phase MLD. By exposing the substrate to alternating solutions (as opposed to vapors) of the MLD precursors, layer-by-layer growth similar to that in SILAR or layer-by-layer sol-gel can be achieved. This technique also yields the benefits of high throughput, low cost, and no vacuum. Additionally, there are many organic materials whose growth via gas phase MLD would be impractical (e.g., due to the difficulty of evaporating the precursors), but which can be readily grown via solution phase MLD.
[0021] While the vast majority of MLD has been performed using vapor deposition techniques, there are notable exceptions, such as the solution-phase demonstration of MLD of polyamides from dissolved precursors. In this example, aromatic polyamides were deposited in a layer-by-layer manner similar to MLD by sequentially exposing the substrate to a solution of a biheterofunctional reagent.
[0022] In a separate gas-phase example, alucone growth from TMA and the homofunctional reagent BDO (butanediol) failed to achieve linear growth because two functional groups on a single BDO molecule reacted simultaneously with the Al-terminated surface (“double reaction”), rendering the surface inactive for further reactions.
[0023] Many other materials also fail to achieve linear growth in gas phase MLD for the same reasons. However, in the liquid phase, various chemistries can be used that prevent reactions at both ends of the bifunctional reagent. Using this approach, controlled layer-by-layer growth of polymers has been performed on both flat substrates (e.g., SiO2 / Si wafers) and porous substrates (e.g., nanoporous alumina).
[0024] Conformal growth on nanoporous alumina has been demonstrated by cross-sectional microscopy. Elemental analysis of the surface layer indicates that the coating penetrates throughout the porous nanostructure of the substrate.
[0025] These results clearly demonstrate that solution-phase methods are capable of conformally coating nanoporous substrates composed of high-aspect ratio features, with precursor residence times within the range of reasonable, scalable methods (1-10 seconds). In this context, the physical similarities between nanoporous alumina substrates and porous LIB electrodes are quite obvious and provide confidence that the technology can conformally coat artificial SEI on the surface of silicon-containing anodes.
[0026] In addition to the unique protection / deprotection chemistry that can be added to the MLD method, other key benefits of the liquid phase method are the ability to employ precursors whose vapor pressure at reasonable temperatures is too low for gas phase MLD methods. For example, more complex sugar alcohols (e.g., erythritol) can be used to generate new alucones in an easy manner. Similarly, longer / larger organic monomers whose intermolecular van der Waals forces prevent evaporation can also be dissolved in a suitable solvent and used. The use of such larger monomer units or appropriately terminated oligomers can greatly enhance the deposition coating rate. For example, in the case of depositing an artificial SEI on a LIB electrode, a 5 nm thick alucone film that is typically deposited by 10 cycles in the case of gas phase MLD can be deposited in only a few cycles in liquid phase MLD by employing larger monomers or prepolymers.
[0027] However, until now, no solution phase techniques have been developed to conformally coat the surface of alloying or converting lithium ion anode materials with organic, inorganic or mixed organic-inorganic materials. A large number of candidate materials can be deposited on the surface of alloying or converting lithium ion anodes in a cost-effective and scalable manner by utilizing various solution phase deposition techniques (e.g., CBD, SILAR, layer-by-layer sol-gel or solution MLD). Specific materials can then be selected to produce an artificial SEI that protects the associated lithium ion battery from the harmful reactions outlined in the previous sections.
[0028] The important advantage of solution phase deposition over vapor phase deposition is that there are many technologies to scale up solution phase deposition to large-scale production. Currently, all LIB manufacturing uses roll-to-roll (R2R) production equipment to produce long electrode rolls, which are eventually cut and packaged as cylinders or pouches. Therefore, any technology that introduces the coating method into LIB manufacturing must also be able to process the entire electrode roll at one time. Fortunately, R2R wet coating technology has been scaled up to large-scale production in many industries. For example, these technologies have been commercialized in the OLED, thin-film solar and membrane industries to the order of millions of square meters per year. The LIB anode and cathode themselves use wet coating, that is, slit casting slurry directly on the foil mesh substrate. R2R solution deposition produces films with thicknesses ranging from single-digit nm to 100 microns on various substrate types and morphologies, and has a high degree of uniformity.
[0029] At a manufacturing scale, R2R solution deposition offers four key advantages over its gas phase counterparts: (1) unlike gas phase, which typically requires high substrate temperatures to prevent precursor condensation, solution phase methods are typically performed at temperatures <100 °C, within the upper temperature processing limit of LIB electrodes, (2) commercial R2R solution deposition methods can be run at line speeds commensurate with the production rates of lithium-ion electrodes, (3) solution phase deposition methods eliminate the expensive capital equipment associated with high vacuum gas phase methods, and (4) the low precursor concentrations required for surface saturation (approximately 1-10 mM), combined with near 100% material utilization means that reagent costs in solution phase are significantly lower than those in gas phase. For these reasons, unlike R2R solution deposition, no R2R gas phase ALD or MLD methods have been successfully commercialized to date for high volume production.
[0030] In addition, the introduction of a more stable and robust artificial SEI layer reduces lithium-metal dendrite formation during high-rate charging. Dendrites are known to be a common cause of fire in LIBs. The coating described herein not only stabilizes the cycling capacity of the conversion anode, but also forms a more uniform physical barrier compared to the prior art SEI where local defects are believed to be the starting point of most dendrites. In order to achieve the typical charging target of 80% state of charge in 15 minutes without compromising safety, a robust electrode coating is necessary. Therefore, the method disclosed in the present invention makes an indispensable contribution to LIB cost reduction and potential safety improvements, which will greatly promote customer acceptance of LIB terminal applications (such as electric vehicles).
[0031] Electrode binders (whether conductive or insulating), while covering a large portion of the active material surface, cannot themselves serve as artificial SEIs because they either fail to block the electron transfer associated with electrolyte reduction in the first place, which results in SEI growth in the first place (as in the case of conductive binders), or they fail to conformally cover the electrode surface (allowing electrolyte to diffuse through or around the binder to reach the electrode surface, the case of both insulating and conductive binders). Examples of conductive binders include, but are not limited to, poly(dioctylfluorene-co-fluorenone-co-methylbenzoate) (PFM) and poly(1-pyrene methyl methacrylate) (PPy). Examples of electrically insulating binders include, but are not limited to, poly(vinylidene fluoride) (PVDF), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).
[0032] Therefore, binder materials cannot meet the need for artificial SEI in conversion anode systems. Failure due to SEI formation (either during the first cycle or during repeated cycles) is essentially inevitable in all conversion anodes unless an improved SEI can be designed that not only withstands the volume expansion of the underlying active material, but also does not consume a large amount of lithium in its own formation. In addition, such a material must be electrolyte-impermeable, lithium-permeable, highly resistive and deposited by a cheap, fast and scalable R2R method.
[0033] In certain aspects, the present disclosure provides a liquid deposition method for producing an artificial solid-electrolyte interface (SEI) on the surface of a fully formed lithium ion battery anode composed of at least a conversion material, the method comprising: (a) transferring the fully formed lithium ion battery anode to a first reaction chamber containing a first liquid solution by a conveying device, wherein the first liquid solution comprises at least a first reagent; (b) exposing the fully formed lithium ion battery anode to the first liquid solution in the first reaction chamber by the conveying device to produce a partially coated layer of the artificial SEI with the at least first reagent chemically bonded to the surface of the lithium ion battery anode; (c) rinsing the partially coated layer of the artificial SEI in the first reaction chamber with a first rinsing solution comprising a first solvent to remove unreacted (d) transferring the fully formed lithium ion battery anode from (d) to a second reaction chamber containing a second liquid solution by the conveying device, the second liquid solution comprising at least a second reagent; (e) exposing the fully formed lithium ion battery anode to the second liquid solution in the second reaction chamber by the conveying device, wherein the at least second reagent reacts with the at least first reagent chemically bonded to the surface of the fully formed lithium ion battery anode to produce the artificial SEI on the surface of the lithium ion battery anode comprising a monolayer, the monolayer comprising a compound produced by the reaction of the at least second reagent with the first reagent; and (f) rinsing the artificial SEI in the second reaction chamber with a second rinsing solution comprising a second solvent to remove unreacted second reagent.
[0034] In certain aspects, the present disclosure relates to a liquid deposition method for producing a thin film artificial SEI coating on a surface of a lithium ion battery anode composed of at least a conversion material, the method comprising: (a) providing the lithium ion battery anode on a conveying device; (b) transferring the lithium ion battery anode to a first reaction chamber containing a first liquid solution by the conveying device, wherein the first liquid solution comprises at least a first reagent; (c) exposing the lithium ion battery anode to the first liquid solution in the first reaction chamber by the conveying device to produce a layer partially coated with the at least first reagent chemically bonded to the surface of the lithium ion battery anode; (d) rinsing the layer in the first reaction chamber with a first rinsing solution comprising a first solvent to remove unreacted (e) transferring the lithium ion battery anode from (d) to a second reaction chamber containing a second liquid solution by the conveying device, the second liquid solution comprising at least a second reagent; (f) exposing the lithium ion battery anode to the second liquid solution in the second reaction chamber by the conveying device, wherein the at least second reagent reacts with the at least first reagent chemically bonded to the surface of the lithium ion battery electrode to produce the thin film coating comprising a monolayer on the surface of the lithium ion battery anode, the monolayer comprising a compound produced by the reaction of the at least second reagent with the first reagent; and (g) rinsing the coating in the second reaction chamber with a second rinsing solution comprising a second solvent to remove unreacted second reagent.
[0035] In certain aspects, the present disclosure relates to a system for coating a thin film artificial SEI comprising metal cones onto the surface of a lithium ion battery anode composed of at least a conversion material, the system comprising: a transport device for transporting the anode to (and from) (a) a first reaction chamber, wherein the anode is exposed to a first liquid solution comprising at least a first reagent, the first reagent comprising a metal organic, to produce a layer comprising adsorbed first reagent on the anode; and (b) a second reaction chamber, wherein the anode having the layer comprising adsorbed first reagent is exposed to a second liquid solution comprising at least a second reagent, the second reagent comprising an organic molecule, wherein the at least second reagent reacts with the first adsorbed reagent to produce the thin film on the surface of the electrode.
[0036] In certain aspects, the present disclosure relates to a system for coating a thin film artificial SEI comprising an organic material onto the surface of a lithium ion battery anode composed of at least a conversion material, the system comprising: a transport device for transporting the anode to (and from) (a) a first reaction chamber, wherein the anode is exposed to a first liquid solution comprising at least a first reagent, the first reagent comprising a first organic molecule to produce a layer comprising adsorbed first reagent on the anode; and (b) a second reaction chamber, wherein the anode having the layer comprising adsorbed first reagent is exposed to a second liquid solution comprising at least a second reagent, the second reagent comprising a second organic molecule that is chemically different from the first organic molecule, wherein the at least second reagent reacts with the first adsorbed reagent to produce the thin film on the surface of the electrode.
[0037] In certain aspects, the present disclosure relates to a system for coating a thin film artificial SEI comprising metal cones onto the surface of a lithium ion battery anode composed of at least a conversion material, the system comprising: a transport device for transporting the anode to (and from) a reaction chamber, wherein: (a) the anode is exposed to a first liquid solution comprising at least a first reagent, the first reagent comprising a metal organic to produce a layer comprising adsorbed first reagent on the anode; and (b) the anode having the layer comprising adsorbed first reagent is exposed to a second liquid solution comprising at least a second reagent, the second reagent comprising organic molecules, wherein the at least second reagent reacts with the first adsorbed reagent to produce an anode comprising a monolayer film coated on the surface of the anode, the monolayer film comprising metal cones produced by the reaction of the metal organic with the organic molecules.
[0038] In certain aspects, the present disclosure relates to a system for coating a thin film artificial SEI comprising an organic material onto the surface of a lithium ion battery anode composed of at least a conversion material, the system comprising: a transport device for transporting the anode to a reaction chamber (and transporting the anode from the reaction chamber), wherein: (a) the anode is exposed to a first liquid solution comprising at least a first organic reagent to produce a layer comprising adsorbed first reagent on the anode; and (b) the anode having the layer comprising adsorbed first reagent is exposed to a second liquid solution comprising at least a second organic reagent, wherein the at least second organic reagent reacts with the first adsorbed reagent to produce an anode comprising a monolayer thin film coated on the surface of the anode, the monolayer thin film comprising the organic material produced by the reaction of the first reagent with the second reagent.
[0039] In certain aspects, the present disclosure relates to a liquid deposition method for coating a thin film artificial SEI comprising metal cones onto a surface of a lithium ion battery anode composed of at least a conversion material, the method comprising: (a) providing the anode into a reaction chamber; (b) exposing the anode to a first liquid solution comprising a first reagent, the first reagent comprising a metal organic to produce a layer comprising adsorbed first reagent on the surface of the anode; and (c) exposing the anode having the absorbed first reagent to a second liquid solution comprising a second reagent, the second reagent comprising an organic molecule, wherein the at least second reagent reacts with the first adsorbed reagent to produce a monolayer film coated on the surface of the anode, the monolayer film comprising the metal cones produced by the reaction of the metal organic with the organic molecules.
[0040] In certain aspects, the present disclosure relates to a liquid deposition method for coating a thin film artificial SEI comprising an organic material onto the surface of a lithium ion battery anode composed of at least a conversion material, the method comprising: (a) providing the anode into a reaction chamber; (b) exposing the anode to a first liquid solution comprising a first organic reagent to produce a layer comprising adsorbed first reagent on the surface of the anode; and (c) exposing the anode having the absorbed first reagent to a second liquid solution comprising a second organic reagent, wherein the at least second organic reagent reacts with the first adsorbed reagent to produce a monolayer film coated on the surface of the anode, the monolayer film comprising the organic material produced by the reaction of the first reagent with the second reagent.
[0041] In certain aspects, the present disclosure relates to a lithium ion battery anode comprising a conversion material comprising a porous microstructure coated with one or more monolayer thin film artificial SEI coatings, wherein the thin film artificial SEI coating comprises metal cones or organic materials, wherein the thin film artificial SEI coating is produced by a liquid phase deposition method described herein. In certain aspects, the present invention relates to a lithium ion battery comprising an anode, the anode consisting of a conversion material coated with a thin film artificial SEI, the thin film artificial SEI comprising metal cones or organic materials, wherein the thin film is produced by a liquid phase deposition method described herein.
[0042] In some embodiments, the method steps provided herein are repeated to produce a continuous growth of multiple stacked monolayers, thereby producing an artificial SEI with a total thickness between 0.5 nanometers (nm) and 100 micrometers (μm). In some embodiments, the thickness of the fully formed lithium ion battery anode is 100 nm to 1,000 μm. In some embodiments, the fully formed lithium ion battery anode has pores with a size ranging from 0.1 nm to 100 μm. In some embodiments, the membrane porosity of the fully formed lithium ion battery anode is 1-99%.
[0043] In some embodiments, the conversion material comprises Si, Sn, Ge, Al, P, Zn, Ga, As, Cd, In, Sb, Pb, Bi, SiO, SnO2 or any combination of these. In some embodiments, the monolayer or stacked monolayer is composed of at least one or more metal cones. In some embodiments, the one or more metal cones are produced by the reaction between a first reagent comprising a metal organic and a second reagent comprising an organic molecule. In some embodiments, the first reagent is a metal organic comprising an organic part and a metal, the metal comprising Al, Zn, Si, Ti, Zr, Hf, Mn and / or V, and the second reagent is an organic molecule comprising: ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol and / or diaminodiphenyl ether. In some embodiments, the artificial SEI produced by the monolayer or stacked monolayers is composed of one or more organic materials. In some embodiments, the one or more organic materials are polymers comprising: polyamide, polyimide, polyurea, polyazomethine, fluoroelastomer, or any combination of these.
[0044] In some embodiments, the conveying device comprises a series of rollers for transferring the fully formed lithium ion battery to the first reaction chamber or the second reaction chamber. In some embodiments, the fully formed lithium ion battery anode is exposed to the first liquid solution and the second liquid solution by immersion, spraying, slot die coating, bath coating or gravure roller coating. In some embodiments, the fully formed lithium ion battery anode comprises an active material, wherein the active material is exposed to the first liquid solution and the second liquid solution by spraying, slot die coating, bath coating or gravure roller coating.
[0045] In some embodiments, the method described herein further comprises sending a first residual solution comprising the first solvent and the unreacted first reagent to a first filtering step to separate the unreacted first reagent from the first solvent; and sending a second residual solution comprising the second solvent and the unreacted second reagent to a second filtering step to separate the unreacted second reagent from the second solvent. In some embodiments, the method further comprises recycling the recovered unreacted first reagent or second reagent back to the first liquid solution or the second liquid solution, respectively; and recycling the recovered first solvent or second solvent back to the first rinse solution or the second rinse solution, respectively. In some embodiments, the first filtering step and the second filtering step are performed using membrane separation, chemical precipitation, ion exchange, electrochemical removal, physical adsorption, flow filtration chromatography, or any combination of these.
[0046] In some embodiments, the first liquid solution and the second liquid solution comprise more than one reagent. In some embodiments, the artificial SEI consists of grains with a length ranging from 0.5 nm to 100 μm in size. In some embodiments, the artificial SEI is crystalline. In some embodiments, the artificial SEI is amorphous. In some embodiments, the elastic modulus of the artificial SEI is between 0.1 GPa and 100 GPa. In some embodiments, the volume elongation at break of the artificial SEI is between 1% and 500%.
[0047] In some embodiments, the molecular weight of the organic molecule in the second reagent is between 10-10,000 Daltons.
[0048] In some embodiments, the lithium ion battery anode comprises an active material deposited on a substrate. In some embodiments, the active material in the lithium ion battery anode is a conversion anode material comprising Si, Sn, Ge, Al, P, Zn, Ga, As, Cd, In, Sb, Pb, Bi, SiO, SnO2, or any combination of these. In some embodiments, the substrate is made of a metal such as copper, aluminum, or stainless steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is a general flow diagram of an embodiment of a method according to the present disclosure. The method includes a rinse / clear step and a filtration step.
[0050] Figure 2 is a schematic diagram of one embodiment of a system for coating a thin film onto the surface of a lithium ion battery anode according to the present disclosure.
[0051] Figure 3is an illustration of a lithium ion battery anode coated with a thin film according to the present disclosure on top of a foil substrate. DETAILED DESCRIPTION
[0052] The present disclosure provides a solution phase deposition method and system for forming an "artificial" SEI (thin film) layer and applying it to the surface of a conversion anode in a battery (e.g., an anode in a lithium ion battery). The present method and system produce an artificial SEI that is superior to conventional electrochemical growth. Such a coating (or nanolayer) produced by the method and system described herein can be flexible and mechanically strong (so as to withstand the volume expansion that usually occurs during the lithiation of such an anode), electrically insulating (so as to prevent electron transfer associated with the reduction of electrolyte molecules adjacent to such an electrode), lithium permeable (so as not to hinder the transfer of lithium ions between such anodes to any associated cathodes, and vice versa) and dense enough to prevent electrolyte molecules from diffusing to the electrode surface through the artificial SEI (which would completely offset the effect of the artificial SEI).
[0053] As used herein, the term "conversion" refers to a material whose crystal structure undergoes a change upon lithium insertion, which is accompanied by the breaking and reforming of chemical bonds on the host material matrix. In some cases, a subset of conversion materials may be referred to as "alloyed" materials. Alloyed materials are those materials in which lithium forms a solid solution or phase mixture with a metallic or semi-metallic host matrix upon insertion.
[0054] The method generally refers to a solution phase (also described as "liquid phase") coating method for depositing a thin film forming an artificial SEI on the surface of a conversion anode material. Such a coated anode can then be paired with an appropriate cathode to produce a full lithium ion battery with improved performance and energy density.
[0055] Figure 3 An example of an embodiment of a coated battery anode according to the present disclosure is shown in FIG. A coated battery conversion anode 300 comprises bound anode constituent active material particles 302 coated with a thin film 303. The thickness of the thin film 303 may be between 0.5 nm and 100 μm. Anode constituent particles 301 are located on top of a foil substrate 301.
[0056] The electrodes as described herein are fully formed (also interchangeably referred to herein as "preformed"). Fully formed electrodes refer to the standard sequence of electrode formation methods, including but not limited to casting a slurry of active and inactive material components onto a foil substrate to form the electrode, followed by drying the electrode, and then calendaring the electrode. In some embodiments, the fully formed electrode does not include calendaring.
[0057] The electrode typically comprises a porous coating of an "active material" on top of a substrate (e.g., foil or sheet). Active material refers to a specific material within a lithium-ion battery electrode that accepts insertion and extraction of lithium during charge and discharge. In some embodiments, the battery electrode is an anode that may be composed of an active material that is a conversion material. The conversion anode material may be composed of elements or compounds including, but not limited to, Si, Sn, Ge, Al, P, Zn, Ga, As, Cd, In, Sb, Pb, Bi, SiO, or SnO2.
[0058] In certain embodiments, substrate can be a continuous substrate, typically in the form of foil or sheet. "Continuous substrate" as used herein refers to a substrate having an aspect ratio of at least 10:1 between its two largest dimensions, and is flexible enough to be wound onto itself in the form of a roll. It can be made of various materials, including but not limited to metals (e.g., copper, aluminum, or stainless steel) or organic materials (e.g., polyimide, polyethylene, polyetheretherketone (PEEK) or polyester, polyethylene naphthalate (PEN)).
[0059] In certain aspects, the methods and systems provided herein relate to creating an artificial SEI layer in a battery that is more resistant to dissolution than current SEIs, has sufficient adhesion to the material or component to be coated, has sufficient mechanical stability, has appropriate electrical resistivity to prevent electrolyte decomposition, while conducting ions (such as, in the case of a battery, lithium ions), and is essentially free of any inter-particle internal resistance.
[0060] exist Figure 1 A simple flow chart of an embodiment of a method according to the present disclosure is shown in FIG. Figure 1 Embodiments are directed to methods of coating a thin film forming an artificial SEI on the surface of a conversion anode, but this description is representative only of components deposited using the methods and systems provided herein and should not be construed as limiting in any way.
[0061] refer to Figure 1 For example, at 100, a conversion anode can be exposed to a first liquid solution comprising one or more first reagents in a first reaction chamber to produce a layer comprising one or more adsorbed first reagents on a surface of the anode.
[0062] The first liquid solution comprises at least a first reagent. The first reagent can be any compound capable of reacting with the material of the anode (i.e., the component to be coated) to form a self-limiting layer. In certain embodiments, the first reagent is a metal organic compound. Examples of such metal organics include, but are not limited to, aluminum tri-sec-butoxide, titanium ethoxide, niobium ethoxide, trimethylaluminum, and zirconium tert-butoxide. In another embodiment, the first reagent comprises an aqueous solution comprising an ionic compound. Examples include, but are not limited to, zinc acetate, cadmium chloride, zinc chloride, zirconium chloride, and zinc sulfate. In some embodiments, the pH of the first solution may vary. In some embodiments, the first liquid solution may be a solution of an ionic compound comprising both a cationic precursor and an anionic precursor that react to form a solid film; in this case, film growth is limited by film-forming reaction kinetics. In some embodiments, the first liquid solution may contain a complexing agent that limits film-forming reaction kinetics. In some embodiments, the first liquid solution may be a solution comprising both a metal organic precursor and an oxidizing precursor that react to form a solid film; in this case, film growth is limited by film-forming reaction kinetics.
[0063] In embodiments where the first reagent is a metal organic, the first liquid solution may further comprise a solvent for dissolving or complexing the first reagent. Preferred solvents include organic solvents such as alcohols (e.g., isopropanol or ethanol), alcohol derivatives (e.g., 2-methoxyethanol), less polar organic solvents (e.g., pyridine or tetrahydrofuran (THF)), or non-polar organic solvents (e.g., hexane and toluene).
[0064] In one embodiment, the first liquid solution is contained within a first reaction chamber. The reaction chamber must be a device large enough to accommodate the amount of liquid solution that receives the electrode and contains the reaction for producing a self-limiting layer. Such devices that can be used as reaction chambers include, but are not limited to, tanks, baths, pans, beakers, and the like.
[0065] The anode can be transferred to the first reaction chamber by a conveyor device. As described in more detail below, the conveyor device can be adjusted and positioned in such a way as to guide or direct the anode into and / or out of the first chamber.
[0066] In certain embodiments, the anode can be completely or partially immersed in the first liquid solution of the first reaction chamber and the second liquid solution of the second reaction chamber, respectively. In other embodiments, the anode can be sprayed with the first liquid solution in the first reaction chamber and the second liquid solution in the second reaction chamber, respectively.
[0067] In another embodiment, the anode can be transmitted below the slot die coater, and the first liquid solution is continuously distributed from the slot die coater to produce a liquid film on the specified area of the anode. The speed of the anode transmission and the flow rate of the fluid through the mold determine the thickness of the liquid film. Then, the solvent can simply evaporate to produce a solid film of the dissolved component, or the liquid film can have a reactant that reacts to precipitate a thin film on the surface of the anode. The resulting solid film can be as thin as an atomic monolayer or as thick as 100 microns. The reaction can occur when the solvent is still present or after the solvent has evaporated. If the residual solvent or solution is retained until after the coating method ends, it can be removed by various techniques (such as scraper, air knife, metering knife or similar technology). The entire slot die coating method can then be repeated to produce a new film of different chemical compositions or simply produce a thicker coating of the same chemical composition. In this case, the reaction chamber only includes the area where the slot die coater is located, and is not necessarily similar to the enclosed space implied by the term "chamber".
[0068] In another embodiment, the anode can be conveyed through the tank and gravure roller containing the coating solution. In this embodiment, the gravure roller is continuously transferred from the dipping tank to the adjacent coil by the coating solution due to the preferential surface tension (wetting) of the coil and the roller. As in the slot die coating, the result is initially a liquid film on the surface of the anode. For example, the composition of a specific solution, coil and roller can affect the surface tension of the fluid on both the coil and the roller, thereby affecting the coating efficiency of the method. Then, the solvent can simply evaporate to produce a solid film of the dissolved component, or the liquid film can have a reactant that reacts to precipitate a thin film on the surface of the anode. The resulting solid film can be as thin as an atomic monolayer or as thick as 100 microns. The reaction can occur when the solvent is still present or after the solvent has evaporated. If the residual solvent is retained until after the coating method ends, it can be removed by various techniques (such as scraper, air knife, metering knife or similar techniques). The entire gravure coating method can then be repeated to produce a new film of different chemical compositions or simply produce a thicker coating of the same chemical composition.
[0069] Multiple consecutive, repeated steps of the same process (i.e., slot die or gravure coating) can be performed with the same or different solutions. The solutions can be separated (e.g., in a first solution, a second solution, etc.) to avoid cross contamination, for example, or to prevent homogeneous nucleation when a heterogeneous film-forming reaction is preferred.
[0070] The conversion anode is exposed to the first liquid solution for a sufficient time ("residence time") to allow one or more first reagents to adsorb onto the anode surface and produce a continuous layer (i.e., a self-limiting layer). Examples of process variables that can affect this step include solution and anode temperature, residence time, and reagent concentration.
[0071] The advantages of the present method and system are that the solvents used have different specific heat capacities and can also serve as heat transfer and precursor transfer media, resulting in faster and more efficient heating of the anode. Precursors dissolved in solution are also much more stable in exposure to air environments than their pure analogs, resulting in improved safety and easier handling.
[0072] Optionally, the anode may undergo a first rinse / clean step 102, whereby excess first reagent from step 100 is removed with a solvent. Here, most or all of the unadsorbed first reagent is removed from the anode surface before the electrode is moved to the next process step. Key process variables include solvent temperature, anode temperature, and residence time. Step 102 is Figure 1 0 is shown as a single step, however, in certain embodiments, this step may be repeated or there may be additional rinse / clear steps to improve first reagent removal.
[0073] The rinsing step may leave just a saturated (ie, purified) first layer on the anode and a residual solution in the reaction chamber comprising the first solvent, unreacted first reagent or reagents, and other reaction byproducts.
[0074] As another optional step, in order to recycle the solvent and any unreacted reagent used in the rinsing step, the residual solution can be sent to a filtering step 103. The filtering step separates the solvent from the unreacted reagent (and any byproducts of reaction). The filtering step also prevents cross contamination between chambers and avoids the slow contamination of the rinsing solution by the reagent during operation. The continuous filtration rinsing bath can not only maintain the purity of the rinsing solvent, but also can be used as a system for material recovery, thereby improving the material utilization efficiency of the method. Any filtering technique known in the art can be used. Preferred techniques include but are not limited to membrane separation, chemical precipitation, ion exchange, electrochemical removal, physical adsorption and flow filtration chromatography.
[0075] The separated solvent may be recycled back to the rinsing step 102 for reuse. Likewise, the filtered unreacted first reagent or reagents may also be recycled back to 100 for further use in the process (not shown).
[0076] Then, in 104, the partially coated conversion anode having the layer comprising the adsorbed first reagent (ie, the self-limiting layer) can be exposed to a second liquid solution comprising a second reagent in a second reaction chamber.
[0077] In some embodiments, the second liquid solution may include an oxidant, such as an oxide or a chalcogenide source, examples of which include, but are not limited to, water, thioacetamide, and sodium sulfide. A solvent may also be present, which may include a polar or non-polar organic solvent or may be only water. In other embodiments, the second liquid solution may also contain a nitrogen-containing reagent, such as ammonia or hydrazine. In some embodiments, the pH of the second solution may also vary.
[0078] The second reagent has a different and unique composition compared to the first reagent.The second reagent is selected to be capable of reacting with the adsorbed first reagent to produce a complete monolayer of the thin film compound coated on the conversion anode.
[0079] In some embodiments, the entire membrane can be formed by exposure to reagents from the conversion anode only from the first liquid solution. In this case, the second solution can be skipped entirely.
[0080] In some embodiments, the compound formed may include metal oxides, such as Al2O3 and TiO2. In other embodiments, the compound formed may include transition metal dichalcogenides (TMDs). Typical examples of such materials follow the chemical formula MX2, where M is a transition metal, such as Mo, W, Ti, etc., and X is S or Se.
[0081] In some embodiments, the compound is composed of any combination of the following polymers: polyethylene oxide (PEO), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), polydimethylsiloxane (PDMS), polyvinyl pyrrolidone (PVP). When combined with a lithium salt (e.g., LiClO4, LiPF6, or LiNO3, etc.), such polymers may produce a solid polymer electrolyte film.
[0082] In some embodiments, the compound may include, for example, a sulfide or selenide of Mo, Ti, or W. These materials vary widely in their electronic properties (e.g., band gaps), and thus can be used to create tailored semiconductor heterojunctions that, for example, will block the electron transfer necessary to degrade reactions in lithium-ion battery operation. Specifically, such a mechanism can be used to block degradation reactions on the surface of the anode.
[0083] In some embodiments, the compound formed can be selected from:
[0084] (a)A x O y A binary oxide of the type wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, and x and y are stoichiometric coefficients;
[0085] (b)A x B yO z A ternary oxide of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and x, y and z are stoichiometric coefficients;
[0086] (c)A w B x C y O z A quaternary oxide of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and w, x, y and z are stoichiometric coefficients;
[0087] (d)A x B y A binary halide of the type wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, B is a halogen, and x and y are stoichiometric coefficients;
[0088] (e)A x B y C z A ternary halide of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, C is a halogen, and x, y and z are stoichiometric coefficients;
[0089] (f)A w B x C y D z A quaternary halide of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, D is a halogen, and w, x, y and z are stoichiometric coefficients;
[0090] (g)A x N y Type binary nitride, wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, and x and y are stoichiometric coefficients;
[0091] (h)A x B y N z A ternary nitride of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and x, y and z are stoichiometric coefficients;
[0092] (i)A w B x C y N z A quaternary nitride of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and w, x, y and z are stoichiometric coefficients;
[0093] (j)A x B y A binary chalcogenide of the type, wherein A is an alkali metal, an alkaline earth metal, a transition metal, a semimetal or a metalloid, B is a chalcogen element, and x and y are stoichiometric coefficients;
[0094] (k)A x B y C z A ternary chalcogenide of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, C is a chalcogen element, and x, y and z are stoichiometric coefficients;
[0095] (l)A w B x C y D z A quaternary chalcogenide of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, D is a chalcogen element, and w, x, y and z are stoichiometric coefficients;
[0096] (m)A x C y Type binary carbide, wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, and x and y are stoichiometric coefficients;
[0097] (n)A x B y O z A binary oxyhalide of the type wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, B is a halogen, and x, y and z are stoichiometric coefficients;
[0098] (o)A x As y A binary arsenide of the type A, wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, and x and y are stoichiometric coefficients;
[0099] (p)A x B y As z A ternary arsenide of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and x, y and z are stoichiometric coefficients;
[0100] (q)A w B x C y As z A quaternary arsenide of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and w, x, y and z are stoichiometric coefficients;
[0101] (r)A x (PO4) y A dibasic phosphate of the type wherein A is an alkali metal, alkaline earth metal, transition metal, semimetal or metalloid, and x and y are stoichiometric coefficients;
[0102] (s)A x B y (PO4) z A tribasic phosphate of the type wherein A and B are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and x, y and z are stoichiometric coefficients; and
[0103] (t)A w B x C y (PO4) z A tetrabasic phosphate of the type wherein A, B and C are any combination of alkali metals, alkaline earth metals, transition metals, semimetals or metalloids, and w, x, y and z are stoichiometric coefficients.
[0104] In the case of a reaction between a non-ionic precursor (e.g., a metal organic) and an oxidant, as in the hydrolysis of trimethylaluminum, the organic moiety is removed and replaced by metal-oxygen-metal bonds until all bonds are fully saturated. In the case of a reaction between two ionic solutions, as in the hydrolysis of Cd 2+ and S 2- In the reaction between solutions of ions, the high solubility product constant of the reaction promotes the precipitation of the ionic compound (in this case, CdS), where the electrode promotes heterogeneous film formation by minimizing the surface energy.
[0105] In some embodiments, the compound formed in the monolayer of the film forming artificial SEI or the monolayer of the stack may include at least one or more metal cones. The one or more metal cones may be produced by the reaction between a first precursor selected from metal organics and a second precursor selected from organic molecules. In some embodiments, the first precursor may be a metal organic. The metal organic may include an organic part and such a metal, and the metal includes but is not limited to Al, Zn, Si, Ti, Zr, Hf, Mn and / or V. In some embodiments, the second precursor may be an organic molecule. In certain embodiments, the organic molecule may include but is not limited to ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol and / or diaminodiphenyl ether.
[0106] In other embodiments, the compound formed in the monolayer of the film forming artificial SEI or the monolayer of the stack may include one or more organic materials. Such one or more organic materials may include but are not limited to polyamide, polyimide, polyurea, polyazine and / or fluoroelastomer. In certain embodiments, the one or more organic materials may be produced by the reaction between the first reagent comprising the first organic molecule and the second reagent comprising the second organic molecule. In certain embodiments, the first organic molecule is chemically different from the second organic molecule.
[0107] In some embodiments, the thickness of the film forming the artificial SEI can be about 0.5 nm-100 μm. For example, the thickness of the film can be in the range of 0.5 nm-10 nm, 10 nm-50 nm, 50 nm-100 nm, 100 nm-500 nm, 500 nm-1 μm, 1 μm-10 μm, 10 μm-50 μm, or 50 μm-100 μm.
[0108] In some embodiments, the thin film forming the artificial SEI can be characterized based on its strength and durability. Thus, the elastic modulus of the thin film produced by the stack of monolayers or monolayers can be at most 100 GPa and at least 0.1 GPa. In other embodiments, the volume elongation at break of the material comprising the thin film produced by the stack of monolayers or monolayers can be at most 500% and at least 1%.
[0109] Similar to step 102, the conversion anode from step 104 is then directed to a second rinse / purge step 106 to remove unadsorbed / unreacted second reagent.
[0110] In some embodiments, steps 100-106 may be repeated any number of times until a thin film coating of desired thickness is formed on the conversion anode. This scheme is indicated by 108, where the anode coated with the thin film is directed back to step 100 for further processing (forming a loop). In some embodiments, these steps will be repeated with different precursors, thereby producing a coating comprising a stack of thin films containing various compounds.
[0111] In addition, during 102 and 106, the rinse or remove solvent can be filtered continuously or periodically so that one or more unreacted reagents can be separated and recovered from the solvent. This filtering step is indicated in steps 103 and 105, respectively. Then, both the precursor and the solvent can potentially be recycled back into the method. Here, the recycling of the solvent is shown by the return arrow. These filtering steps will save significant material costs during the life of the equipment. For each washing and rinsing step, a filtering step can be incorporated into the design. The filtering technology is preferably adjusted to the type of reagent used in steps 100 and 104. For example, an aqueous ionic solution may require a filter column of the type used in a deionizer to be fully filtered. However, organometallic compounds can be better removed by a tangential flow filtration system, for example, which excludes by molecular weight.
[0112] exist Figure 2 A schematic diagram of an embodiment of a system for coating a thin film that forms an artificial SEI onto the surface of a conversion anode is shown in FIG. Figure 2 In the diagram, the reaction chamber is shown as a continuous tank or bath containing the reaction solution; the electrodes are transported into the reaction chamber with the help of a transport device. Figure 2 Embodiments of the present invention relate to methods of coating a thin film that forms an artificial SEI onto a battery electrode surface, but this description represents only components coated using the methods and systems provided herein and should not be construed as being limiting in any way.
[0113] Figure 2 The conveying device is particularly suitable and adapted to guide or direct the conversion anodes in such a way as to enter and leave the first reaction chamber and the second reaction chamber in a continuous manner.
[0114] The preferred automated conveying equipment comprises a series of rollers, such as tension rollers, which are positioned in a manner to guide or direct the electrode to enter and leave the first reaction chamber and the second reaction chamber. In this way, the system can provide a continuous liquid deposition method for coating the film forming artificial SEI on the surface of the electrode. A series of rollers 202a-i are driven by a conveying motor (not shown). Rollers 202a-i operate and orient in a manner that enables conversion anode 201 to be transmitted by the system, as discussed in more detail below. System 200 also comprises a series of chambers 205, 207, 215 and 217.
[0115] In certain embodiments, the first reaction chamber and the second reaction chamber may include a sensor for determining or measuring the volume of the first liquid solution or the second liquid solution in each reaction chamber or the concentration of the precursor in each reaction chamber. In addition, the first reaction chamber and the second reaction chamber may also include a regulating valve actuated by a sensor electronics. When a sensor (e.g., a float switch) determines that the liquid solution is too low, the valve opens, allowing more liquid solution to flow into the reaction chamber from another source. In some cases, a pump (e.g., a peristaltic pump) is used to drive the liquid solution into the reaction chamber. When the sensor determines that the liquid solution is at a desired level, the valve closes to prevent excess liquid solution from flowing into the reaction chamber. In some cases, if the sensor determines that the liquid solution is too high in the reaction chamber, the valve opens, allowing excess liquid to flow out of the reaction chamber. In the case where the sensor detects the concentration of the precursor, when the concentration of the tank precursor solution is detected to be low, the valve can expose the tank to a stock solution of a high precursor concentration, and vice versa. An example of such a sensor is an ion selective electrode.
[0116] In a further embodiment, the system comprises a first rinsing chamber located between the first reaction chamber and the second reaction chamber. The first rinsing chamber contains a first rinsing solution, wherein the first rinsing solution comprises a first solvent for rinsing the anode conveyed to the first rinsing chamber by the conveying device to produce a saturated first layer on the anode, and a first residual solution comprising the first solvent and unreacted first reagent.
[0117] Likewise, the system may further comprise a second rinsing chamber located after the second reaction chamber. The second rinsing chamber contains a second rinsing solution, wherein the second rinsing solution comprises a second solvent and is used to rinse the electrode transported to the second rinsing chamber by the transport device to generate a thin film forming an artificial SEI coated on the conversion anode.
[0118] Chamber 205 is a first reaction chamber that contains a first liquid solution comprising a first reagent and a solvent.
[0119] Chamber 207 is a first rinsing chamber located after first reaction chamber 205, containing a first rinsing solution comprising a first solvent. A first filtration device 209 is connected to first rinsing chamber 207. First filtration device 209 has a residue pipe 213 and a permeate collection pipe 211 connected to first rinsing chamber 207.
[0120] Another chamber 215 is a second reaction chamber located after the first rinsing chamber 207 and contains a second liquid solution including a second reagent and a solvent.
[0121] Chamber 217 is a second rinsing chamber located after second rinsing chamber 215. Second rinsing chamber 217 contains a second rinsing solution, which contains a solvent. Second filtration device 219 is connected to second rinsing chamber 217. Second filtration device 219 has a residue pipe 223 and a permeate collection pipe 221 connected to second rinsing chamber 217.
[0122] System 200 further comprises valves 225a-d located on each chamber 205, 207, 215 and 217, respectively. Valves 225a-d are connected to a supplementary source (not shown), which provides additional first liquid solution, second liquid solution, first reagent, second reagent or solvent, respectively, as in the case of the first chamber 215 and the second chamber 215, when needed, or provides more first rinsing solution or second rinsing solution, respectively, as in the case of the first rinsing chamber 207 and the second rinsing chamber 217. Valves 225a-d can be electrically actuated and opened by the triggering of a sensor (not shown), which is suitable for monitoring or measuring the volume or concentration of the liquid solution in the chamber. The sensor can be immersed in the liquid solution of each chamber.
[0123] In operation, the first part of the electrode 203 is first placed on the first roller 202a, which is part of the conveyor 201. Typically, the first part is attached to the guide material strung together by the rest of the rollers 202b-i, for example, by glue or tape. In this way, the guide material can guide the electrode through the conveyor 201 during the method. Once the portion of the electrode placed on the roller 202a is transferred to the roller 202i or when the coating of the entire electrode is completed, the guide material can then be removed from the electrode. An example of such a guide material can be from a previous electrode roll. Before coating a specific electrode, the previous roll of the electrode may have had a long tail length without active material (only foil). Once the previous roll has been processed, the residue is left on the conveyor, and the active material can be cut and removed. Then, the residue will be used as a guide to guide the next electrode roll through the conveyor.
[0124] Thus, the first portion of the electrode 203 is conveyed into the first reaction chamber 205 by the movement of the second roller 202b also located in the first reaction chamber 205. The first portion of the electrode 203 is exposed to the first liquid solution in the first reaction chamber 205 to produce a self-limiting layer containing the adsorbed first reagent on the surface of the first portion of the electrode. The first portion of the electrode 203 stays in the first reaction chamber 205 for a certain residence time so that the reaction occurs. Once the reaction is substantially completed, the first portion of the electrode 203 is removed from the first reaction chamber 205 by moving upward to the third roller 202c.
[0125] When this occurs, a second portion of the electrode 203 is transferred into the first reaction chamber 205. The transfer apparatus is operated in a continuous manner until a desired amount of the electrode is coated with the thin film that forms the artificial SEI.
[0126] Returning to the first portion of the electrode 203, the first portion is then transferred to the first rinsing chamber 207 by the movement of the fourth roller 202D also located in the first rinsing chamber 207. The first rinsing chamber 207 contains a first rinsing solution comprising a first solvent for rinsing the electrode 203 to produce a saturated first layer on the electrode and a first residual solution comprising the first solvent and unreacted first reagent.
[0127] The system may also include a filter for separating the unreacted reagent from the solvent in the first rinse solution and the second rinse solution. The filter may be any device capable of such separation. Preferably, the filter is selected from one of the following: a membrane, a filter column or a chromatographic column, a chemical or electrochemical separation tank or an adsorption column.
[0128] When needed, the first rinsing solution is sent to the first filter device 209 to separate the unreacted first reagent from the first solvent.Compared with the first rinsing solution, the first filter device 209 produces a permeate stream rich in unreacted first reagent and depletes the first solvent and a residual stream rich in the first solvent and depletes the unreacted first reagent.The permeate stream is collected in the permeate collection tube 211, which can be recycled or sent back to the first reaction chamber 205.The residual stream is recycled back to the first rinsing chamber 207 via the residual pipeline 213.Filter device 209 can be operated periodically or continuously.Then, by moving upwards to the 5th roller 202e, the first part of electrode 203 is taken out from the first rinsing chamber 207 from the first rinsing chamber 207.
[0129] The first portion of the electrode 203 is then transferred into the second reaction chamber 215 by moving downward to the sixth roller 202F, which is also located in the second reaction chamber 215. The second reaction chamber 215 contains a second liquid solution, which contains at least a second reagent. Within the second reaction chamber 215, the electrode 203 is exposed to the second liquid solution, which reacts with the first adsorbed reagent to produce a monolayer film coated on the surface of the electrode. After the reaction is substantially complete, the first portion of the electrode 203 is then removed from the second reaction chamber 215 by moving upward to the seventh roller 202g.
[0130] Next, the first portion of the electrode 203 is transferred to the second rinsing chamber 217 by moving downward to the eighth roller 202h also located in the second rinsing chamber 217. The second rinsing chamber 217 contains a second rinsing solution comprising a second solvent for rinsing the electrode to produce a purified single-layer film coated on the surface of the anode 203 and a second residual solution comprising the second solvent and unreacted second reagent.
[0131] Similar to the first rinse solution, the second rinse solution can be sent to the second filtration device 219. Compared with the second rinse solution, the second filtration device 219 produces a permeate stream rich in unreacted second reagent and depleted of second solvent and a residual stream rich in second solvent and depleted of unreacted second reagent. The permeate stream is collected in the permeate collection pipe 221, which can be recycled or sent back to the second reaction chamber 215. The residual stream is recycled back to the second rinse chamber 217 via the residual pipe 223. The filtration device 219 can be operated periodically or continuously.
[0132] Finally, the first portion of the anode 203 is removed from the second rinsing chamber 217 which is transferred upward to the ninth roller 202i. From here, the first portion can be collected or rolled up until the remainder of the desired portion of the anode is coated with the thin film that forms the artificial SEI.
[0133] The present disclosure and Figure 2 An embodiment similar to the embodiment described in can include replacing bath deposition chambers 205 and 215 with slot die or gravure coating chambers (not shown). In such an embodiment, rinsing chambers 207 and 217 may or may not be present, depending on the need for a rinsing step. In such an embodiment, or even in Figure 2 In the embodiment described in , excess solution removal techniques (e.g., air knife, scraper, metering knife, or similar techniques) may be used instead of the rinsing step. In another embodiment, 215 may not be present at all, as the entire deposition reaction may be performed in 205. Thus, the apparatus of the present disclosure (both with respect to deposition apparatus and transport apparatus) may be considered modular and assembled in any particular manner to facilitate a particular solution deposition method.
[0134] The method of the present disclosure can be implemented using or with the aid of a computer system. The computer system can be involved in many different aspects of the operation of the present method, including but not limited to adjusting various aspects of the conveying device, such as guiding the movement of the conveying device by moving the components to be coated into and out of the reaction chamber; by controlling the timing of the opening and closing of the valve; by detecting the volume of the liquid through the sensor reading, guiding the liquid (such as reagents and buffer) to flow into the reaction chamber; and adjusting the pump. In some aspects, the computer system is implemented to automate the method and system disclosed herein.
[0135] The computer system may include a central processing unit (CPU, also referred to herein as a "processor" and "computer processor"), which may be a single-core or multi-core processor, or multiple processors for parallel processing. The computer system may also include a memory or memory location (e.g., random access memory, read-only memory, flash memory), an electronic storage unit (e.g., a hard disk), a communication interface for communicating with one or more other systems (e.g., a network adapter), and peripheral devices (e.g., a cache, other memory, data storage, and / or an electronic display adapter). The memory, storage unit, interface, and peripheral devices communicate with the CPU via a communication bus (solid line) (e.g., a motherboard). The storage unit may be a data storage unit (or data repository) for storing data. The computer system may be operably coupled to a computer network ("network") by means of a communication interface. The network may be the Internet, the Internet and / or an extranet, or an intranet and / or an extranet that communicates with the Internet. In some cases, the network is a telecommunications and / or data network. The network may include one or more computer servers that may implement distributed computing, such as cloud computing. In some cases, the network may implement a peer-to-peer network with the aid of a computer system, which may enable devices coupled to the computer system to behave as clients or servers.
[0136] The CPU can execute a series of machine-readable instructions, which can be embodied in a program or software. The instructions can be stored in a memory location (e.g., a memory). Examples of operations performed by the CPU can include fetching, decoding, executing, and writing back.
[0137] The storage unit may store files, such as drivers, libraries, and saved programs. The storage unit may store stored programs and recorded sessions generated by a user, as well as one or more outputs associated with the program. The storage unit may store user data, such as user preferences and user programs. In some cases, the computer system may include one or more additional data storage units, which are external to the computer system, such as located on a remote server that communicates with the computer system via an intranet or the Internet.
[0138] The computer system can communicate with one or more remote computer systems through a network. For example, the computer system can communicate with the remote computer system of a user (e.g., an operator). The example of a remote computer system includes a personal computer (e.g., a portable PC), a tablet or a tablet PC (e.g., an Apple® iPad, a Samsung® Galaxy Tab), a phone, a smart phone (e.g., an Apple® iPhone, an Android-enabled device, a Blackberry®) or a personal digital assistant. A user can access the computer system through a network.
[0139] The methods described herein can be implemented by machine (e.g., computer processor) executable code stored in an electronic storage location (e.g., memory or electronic storage unit) of a computer system. Machine executable or machine readable code can be provided in the form of software. During use, the code can be executed by a processor. In some cases, the code can be retrieved from a storage unit and stored on a memory for easy access by a processor. In some cases, an electronic storage unit can be excluded and machine executable instructions can be stored on a memory.
[0140] The code may be precompiled and configured for use with a machine having a processor suitable for executing the code, or may be compiled during runtime. The code may be supplied in a programming language, which may be selected to enable the code to be executed in a precompiled or compiled manner.
[0141] The various aspects of the system and method provided herein (e.g., computer system) can be embodied in programming. Various aspects of the present technology can be considered as "products" or "articles", which are generally in the form of machine (or processor) executable code and / or related data, which are carried on a machine-readable medium or embodied in a machine-readable medium. The machine executable code can be stored on an electronic storage unit, such as a memory (e.g., read-only memory, random access memory, flash memory) or a hard disk. "Storage" type media can include any or all tangible memories of computers, processors, etc. or their associated modules, such as various semiconductor memories, tape drives, disk drives, etc., which can provide non-temporary storage for software programming at any time. All or part of the software can sometimes communicate through the Internet or various other telecommunication networks. For example, such communication can enable software to be loaded from one computer or processor to another computer or processor, for example, from a management server or host to a computer platform of an application server. Therefore, another type of medium that can carry software elements includes light, electricity, and electromagnetic waves, such as through wired and optical landline networks and through various air links across the physical interface between local devices. Physical elements that carry such waves (e.g., wired or wireless links, optical links, etc.) can also be considered as media that carry software. As used herein, unless limited to non-temporary, tangible "storage" media, terms such as computer or machine "readable media" refer to any medium that participates in providing instructions to a processor for execution. Therefore, machine-readable media (e.g., computer executable code) can take many forms, including but not limited to tangible storage media, carrier media, or physical transmission media. Non-volatile storage media include, for example, optical or magnetic disks, such as any storage device in any one or more computers, etc., such as can be used to implement the databases shown in the accompanying drawings, etc. Volatile storage media include dynamic memory, such as the main memory of such a computer platform. Tangible transmission media include coaxial cables; copper wires and optical fibers, including wires that comprise buses within a computer system. Carrier transmission media can take the form of electrical signals or electromagnetic signals or sound waves or light waves, such as those generated during radio frequency (RF) and infrared (IR) data communications. Thus, common forms of computer-readable media include, for example, a floppy disk, a diskette, a hard disk, a magnetic tape, any other magnetic medium, a CD-ROM, a DVD or DVD-ROM, any other optical medium, a punched card stock tape, any other physical storage medium with a pattern of holes, a RAM, a ROM, a PROM and an EPROM, a FLASH-EPROM and any other memory chip or cartridge, a carrier wave that transmits data or instructions, a cable or link that transmits such a carrier wave, or any other medium from which a computer can read programming code and / or data. Many of these forms of computer-readable media can participate in carrying one or more sequences of one or more instructions to a processor for execution.
[0142] The computer system may include or communicate with an electronic display comprising a user interface (UI) for providing, for example, one or more sample analysis results. Examples of UFs include, but are not limited to, graphical user interfaces (GUIs) and web-based user interfaces.
[0143] The methods and systems provided above are now further described by the following examples, which are intended to be illustrative and not intended to be limiting of the scope or underlying principles in any way. Example
[0144] Example 1: Coating a thin film on a Si-containing anode
[0145] Aspects of the present disclosure describe the use of a solution phase process to deposit a novel conformal thin film coating directly and through the microstructure of a formed electrode, replacing the naturally formed SEI on a bare Si-containing anode with an "artificial SEI" layer. The method combines a silicon-graphite composite anode material and a conductive or insulating binder material with a thin film solution deposited coating. Specific materials for use as solution phase deposited coatings are further described herein.
[0146] In this embodiment, the active material within the silicon-graphite composite anode is combined with an inorganic or polymeric binder that is either electrically conductive or insulating in nature.
[0147] In this embodiment, the Si-graphite composite active material is composed of 50% silicon and 50% graphite. The Si-graphite composite anode is produced by casting a slurry containing the above-mentioned active material, a conductive or insulating adhesive binder (such as PPy or PVDF, respectively), an additional conductive additive (such as conductive carbon) and an appropriate suspension solvent. The slurry is cast onto a foil collector made of a metal (such as Cu). After the solvent evaporates from the cast slurry, the resulting active material composite anode film can be calendered to a final porosity of 10-50% and a thickness between 10-100 microns.
[0148] In this example, four specific candidate materials can then be used as coatings on the rolled Si-graphite composite anode: AlGL (Aluminum / Glycerol Alucone), AlHQ (Aluminum / Hydroquinone Alucone), AlXY (Aluminum / Xylitol Alucone), Aramid (Kevlar TM type).
[0149] The first two materials (AlGL and AlHQ) were specifically chosen because they were previously demonstrated to be effective as artificial SEI in composite Si-graphite electrodes when applied by gas-phase MLD. Transferring the deposition of these materials to the solution phase represents a relatively low-risk route to demonstrate the feasibility of solution-phase coating methods in protecting Si anode surfaces.
[0150] The latter two materials (AlXY and aramid) represent exciting new examples of coatings that are currently not feasible or difficult to deposit by vapor phase techniques. Xylitol is a five-carbon sugar alcohol analog of glycerol. It has a near-zero vapor pressure up to 200°C, making it impossible to use for vapor phase MLD. However, xylitol can be slightly soluble in a variety of polar solvents, which means that it can be used for solution phase MLD methods. The reason for using xylitol is that its five-carbon chain (and five associated hydroxyl groups) will greatly enhance the branching of its corresponding alucone. This enhanced branching is then expected to improve the fracture toughness and impermeability of the alucone to solvents. When comparing AlEG with AlGL, the same improvement in mechanical properties with increased branching can be observed. The fully saturated carbon network in AlXY can also promote good electronic resistivity. Finally, the high level of branching can also produce a significant mass increase per cycle, which may ultimately lead to a lower number of deposition cycles required to produce a total film thickness approaching 5 nm.
[0151] Aramids have been known for decades for their excellent fracture toughness. As one of the most fracture-resistant polymers known, Kevlar TM Poly(p-phenylene terephthalamide) (PPTA) can withstand the volume expansion of the underlying silicon anode. In addition, recent studies on grafted polymers on flat Si substrates have shown significant improvements in capacity retention. However, grafting polymers formed onto surfaces in calendered porous electrodes is difficult due to poor diffusion of large polymers through tortuous paths. For this reason, MLD prefers to grow polymers from smaller monomers or oligomers that are less likely to face such mass transport problems.
[0152] Deposition of PPTA from the homofunctional reagents terephthaloyl chloride (TC) and p-phenylenediamine (PDA) by vapor phase MLD has been attempted, however, this method demonstrated irregular growth rates, which may be due to "double reaction" of TC with adjacent amine sites leading to reaction termination. In contrast, unique chemistry can be employed in the solution phase to ensure that only one functional group per molecule per cycle will react, which will improve controlled MLD growth.
[0153] An example of a specific composition of a Si-graphite composite anode to be coated via solution phase MLD with one or more of the four aforementioned candidate coating materials would have 44% of Hitachi Mage TM Approximate composition of a mixture of graphite, 44% 50-70 nm nano / amorphous Si, 2% "C45" carbon conductive additive and 10% conductive binder.
[0154] At 50% active material Si content, the electrode formulation is expected to have a weight capacity of about 1600 mAh / g. An example of a reasonable cathode paired with such an anode is an approximately 60 micron thick NMC532 cathode with a capacity of about 150 mAh / g 1C. Then to produce a matching anode with a capacity ratio of about 1.3:1 anode: cathode, the above Si-graphite composite anode will need to be scaled to the appropriate thickness. At 1600 mAh / g and an assumed calendering porosity of about 40%, the anode is about 18-20 microns thick.
[0155] For a full lithium ion battery consisting of the above anode and cathode pair, a separator (such as Celgard 2325) and an electrolyte (such as 1.2M LiPF6 in 3:7 EC:EMC) can be used.
[0156] An example of a cycling protocol for a lithium ion battery of the above configuration includes cycling between full cell potentials of 3 and 4.1 V at charge or discharge rates between C / 10 and 5C.
[0157] In the context of this example, the thickness target for all candidate coating materials on the electrode is 5 nm. In contrast to the method developed for coating flat Si wafers, it may be necessary to extend the residence time of the precursor to promote diffusion of the precursor throughout the tortuous morphology of the anode. However, such a residence time is unlikely to exceed 10 seconds.
[0158] A portion of each coated anode can be retained and potted in conductive epoxy and polished for cross-sectional analysis by SEM-EDX. EDX elemental analysis of Al in alucone will help demonstrate penetration of the coating material. Small portions of the electrode can be sliced and harvested for TEM analysis. TEM provides a better understanding of the uniformity and conformality of the coating on individual particles. Likewise, EDX can be used to perform elemental analysis. Entire portions of the electrode can also be digested into acid and studied by ICP; for example, elemental analysis of Al in the ICP solution is expected to vary with the thickness and conformality of the alucone coating.
[0159] Coating process parameters can be adjusted to improve coating quality and uniformity, or other techniques (e.g., electrode surface pretreatment, such as plasma or ozone pretreatment) can be employed to improve liquid film wetting or final film adhesion. Some cells can also be cycled at 1C under an "aggressive" cycling regime of 2.7-4.2V.
[0160] It should be understood from the above that although specific implementations have been illustrated and described, various modifications may be made thereto and it is contemplated herein. The disclosure is also not intended to be limited by the specific examples provided in the specification. Although certain embodiments have been described with reference to the above description, the description and description of the preferred embodiments herein are not meant to be interpreted in a limiting sense. In addition, it should be understood that all aspects of the disclosure are not limited to the specific descriptions, configurations or relative proportions described herein, which depend on various conditions and variables. Various modifications in the form and details of the embodiments will be apparent to those skilled in the art. Therefore, it can be expected that the disclosure will also cover any such modifications, variations and equivalents.
Claims
1. A liquid phase deposition method for producing an artificial solid-electrolyte interface on the surface of a fully formed lithium-ion battery anode consisting of at least a conversion material, wherein the conversion material comprises Si, Sn, Ge, Al, P, Zn, Ga, As, Cd, In, Sb, Pb, Bi, SiO, SnO2 or any combination of these, the method comprising: (a) transferring the fully formed lithium ion battery anode to a first reaction chamber containing a first liquid solution by a conveying device comprising a series of rollers, the first liquid solution comprising at least a first reagent, the fully formed lithium ion battery anode comprising an active material deposited on a continuous substrate, and the first reagent comprising a metal organic, the metal organic comprising at least one of Al, Zn, Si, Ti, Zr, Hf, Mn or V; (b) exposing the fully formed lithium ion battery anode to the first liquid solution in the first reaction chamber via the delivery device to produce a partially coated layer of the artificial solid-electrolyte interface with the at least first reagent chemically bonded to the surface of the lithium ion battery anode; (c) rinsing the partially coated layer of the artificial solid-electrolyte interface in the first reaction chamber with a first rinsing solution comprising a first solvent to remove unreacted first reagent; (d) transferring the fully formed lithium ion battery anode from (c) to a second reaction chamber containing a second liquid solution by the conveying device, wherein the second liquid solution comprises at least a second reagent, wherein the second reagent comprises an organic molecule, wherein the organic molecule comprises at least one of ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol or diaminodiphenyl ether; (e) exposing the fully formed lithium ion battery anode to the second liquid solution in the second reaction chamber via the delivery device, wherein the at least second reagent reacts with the at least first reagent chemically bonded to the surface of the fully formed lithium ion battery anode to produce the artificial solid-electrolyte interface on the surface of the lithium ion battery anode comprising a monolayer comprising one or more metal cones produced by the reaction of the at least second reagent with the first reagent; and (f) rinsing the artificial solid-electrolyte interface in the second reaction chamber with a second rinsing solution comprising a second solvent to remove unreacted second reagent.
2. The method of claim 1, wherein steps (a)-(f) are repeated to produce a continuous growth of multiple stacked monolayers to produce an artificial solid-electrolyte interface with a total thickness between 0.5 nanometers (nm) and 100 micrometers (μm).
3. The method of claim 1 or claim 2, wherein the fully formed lithium ion battery anode in step (a) has a thickness of 100 nm to 1,000 μm.
4. The method of any one of claims 1-3, wherein the fully formed lithium ion battery anode in step (a) has pores with sizes ranging from 0.1 nm to 100 μm.
5. The method of any one of claims 1-4, wherein the fully formed lithium ion battery anode in (a) has a membrane porosity of 1-99%.
6. The method of claim 1, wherein the one or more metal cones are produced by a reaction between a first reagent comprising a metal organic and a second reagent comprising an organic molecule.
7. The method of claim 6, wherein the first reagent is a metal organic comprising an organic moiety and a metal, the metal comprising Al, and the organic molecule comprises: glycerol, erythritol, xylitol, sorbitol, mannitol, or hydroquinone.
8. The method of any one of claims 1-7, wherein the artificial solid-electrolyte interface created by the monolayer or stacked monolayers consists of one or more organic materials.
9. The method of any one of claims 1-7, wherein the series of rollers is used to transfer the fully formed lithium ion battery to the first reaction chamber or the second reaction chamber in (a) and (d).
10. The method of any one of claims 1-7, wherein the fully formed lithium ion battery anodes of (b) and (e) are exposed to the first and second liquid solutions by immersion, spraying, slot die coating, bath coating, or gravure roll coating.
11. The method of any one of claims 1-7, wherein the active material is exposed to the first liquid solution and the second liquid solution by spray coating, slot die coating, bath coating, or gravure roll coating.
12. The method of any one of claims 1-7, further comprising: sending a first residual solution comprising the first solvent and unreacted first reagent to a first filtration step to separate the unreacted first reagent from the first solvent; and The second residual solution comprising the second solvent and unreacted second reagent is sent to a second filtration step to separate the unreacted second reagent from the second solvent.
13. The method of claim 12, further comprising: recycling the recovered unreacted first reagent or second reagent back to the first liquid solution or the second liquid solution, respectively; and The recovered first solvent or second solvent is recycled back to the first rinse solution or second rinse solution, respectively.
14. The method of claim 12, wherein the first filtration step and the second filtration step are performed using membrane separation, chemical precipitation, ion exchange, electrochemical removal, physical adsorption, flow filtration chromatography, or any combination of these.
15. The method of any one of claims 1-7, wherein the first liquid solution and the second liquid solution comprise more than one reagent.
16. The method of any one of claims 1-7, wherein the artificial solid-electrolyte interface consists of grains with a length ranging in size from 0.5 nm to 100 μm.
17. The method of any one of claims 1-7, wherein the artificial solid-electrolyte interface is a crystal.
18. The method of any one of claims 1-7, wherein the artificial solid-electrolyte interface is amorphous.
19. The method of any one of claims 1-7, wherein the elastic modulus of the artificial solid-electrolyte interface is between 0.1 GPa and 100 GPa.
20. The method of any one of claims 1-7, wherein the artificial solid-electrolyte interface has a volume elongation at break between 1% and 500%.
21. A liquid phase deposition method for coating an artificial solid-electrolyte interface comprising metal cones onto the surface of a fully formed lithium ion battery anode composed of a silicon-graphite composite material, the method comprising: (a) exposing the fully formed lithium ion battery anode to a first liquid solution comprising a first reagent comprising a metal organic to produce a partially coated layer of the artificial solid-electrolyte interface with the first reagent chemically bonded to the surface of the fully formed lithium ion battery anode; and (b) exposing the fully formed lithium ion battery anode having the partially coated layer of the artificial solid-electrolyte interface to a second liquid solution comprising a second reagent comprising organic molecules, wherein at least the second reagent reacts with the first reagent chemically bonded to the surface of the fully formed lithium ion battery anode to produce the artificial solid-electrolyte interface comprising a monolayer, wherein the monolayer comprises the metal cones produced by the reaction of the metal organic with the organic molecules.
22. The method of claim 21, wherein the metal organic comprises Al, Zn, Si, Ti, Zr, Hf, Mn, V, or any combination thereof.
23. The method of claim 21, wherein the organic molecule comprises ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol, diaminodiphenyl ether, or any combination thereof.
24. A liquid phase deposition method for coating an artificial solid-electrolyte interface comprising an organic material onto the surface of a fully formed lithium ion battery anode composed of a silicon-containing material, the method comprising: (a) exposing the fully formed lithium ion battery anode to a first liquid solution comprising a first organic reagent to produce a partially coated layer of the artificial solid-electrolyte interface with the first organic reagent chemically bonded to the surface of the fully formed lithium ion battery anode; and (b) exposing the fully formed lithium ion battery anode having the partially coated layer of the artificial solid-electrolyte interface to a second liquid solution comprising a second organic reagent, wherein at least the second organic reagent reacts with the first organic reagent chemically bonded to the surface of the fully formed lithium ion battery anode to produce the artificial solid-electrolyte interface comprising a monolayer, wherein the monolayer comprises the organic material produced by the reaction of the first organic reagent with the second organic reagent, wherein the organic material comprises a polymer material composed of an aromatic polyamide.
25. The method of any one of claims 21-24, wherein the exposing in (a) and (b) occurs in a single reaction chamber.
26. A liquid phase deposition method for producing a thin film artificial solid-electrolyte interface coating on the surface of a lithium ion battery anode composed of at least one of Si, Ge or Sn, the method comprising: (a) providing the lithium ion battery anode onto a conveyor apparatus comprising a series of rollers; (b) transferring the lithium ion battery anode to a first reaction chamber containing a first liquid solution by the conveying device, wherein the first liquid solution comprises at least a first reagent, the lithium ion battery anode comprises an active material deposited on a continuous substrate, and the first reagent comprises a metal organic; (c) exposing the lithium ion battery anode to the first liquid solution in the first reaction chamber via the delivery device to produce a layer partially coated with the at least first reagent chemically bonded to the surface of the lithium ion battery anode; (d) rinsing the layer in the first reaction chamber with a first rinsing solution comprising a first solvent to remove unreacted first reagent; (e) transferring the lithium ion battery anode from (d) to a second reaction chamber containing a second liquid solution by the conveying device, wherein the second liquid solution comprises at least a second reagent, wherein the second reagent comprises an organic molecule; (f) exposing the lithium ion battery anode to the second liquid solution in the second reaction chamber via the delivery device, wherein the at least second reagent reacts with the at least first reagent chemically bonded to the surface of the lithium ion battery anode to produce the thin film artificial solid-electrolyte interface coating comprising a monolayer on the surface of the lithium ion battery anode, the monolayer comprising one or more metal cones produced by the reaction of the at least second reagent with the first reagent; and (g) rinsing the coating in the second reaction chamber with a second rinsing solution comprising a second solvent to remove unreacted second reagent.
27. A system for coating an artificial solid-electrolyte interface comprising metal cones onto the surface of a lithium ion battery anode consisting of at least a conversion material, wherein the conversion material comprises Si, Sn, Ge, Al, P, Zn, Ga, As, Cd, In, Sb, Pb, Bi, SiO, SnO2, or any combination of these, the system comprising: A conveying apparatus comprising a series of rollers for conveying the anodes to: (a) a first reaction chamber, wherein the anode is exposed to a first liquid solution comprising at least a first reagent, the first reagent comprising a metal organic, to produce a layer comprising adsorbed first reagent on the anode, wherein the metal organic comprises at least one of Al, Zn, Si, Ti, Zr, Hf, Mn or V; and (b) a second reaction chamber, wherein the anode having a layer comprising an adsorbed first reagent is exposed to a second liquid solution comprising at least a second reagent, the second reagent comprising an organic molecule, wherein at least the second reagent reacts with the adsorbed first reagent to produce the artificial solid-electrolyte interface on the surface of the anode, wherein the organic molecule comprises: at least one of ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol or diaminodiphenyl ether.
28. A system for coating an artificial solid-electrolyte interface comprising an organic material onto the surface of a lithium-ion battery anode consisting of at least a silicon-containing conversion material, the system comprising: A conveying device for conveying the anode to: (a) a first reaction chamber, wherein the anode is exposed to a first liquid solution comprising at least a first reagent, the first reagent comprising a first organic molecule, to produce a layer comprising adsorbed first reagent on the anode; and (b) a second reaction chamber, wherein the anode having a layer comprising an adsorbed first reagent is exposed to a second liquid solution comprising at least a second reagent, the second reagent comprising a second organic molecule chemically different from the first organic molecule, wherein at least the second reagent reacts with the adsorbed first reagent to produce a film comprising an organic material on the surface of the anode, wherein the organic material comprises a polymer material of at least one of a polyamide, a polyurea, a polyazineimide, or a fluoroelastomer.
29. The system of claim 27, wherein the series of rollers are used to guide the anode to the first and second reaction chambers.
30. The system of any one of claims 27-29, wherein the first reaction chamber and the second reaction chamber are in the form of a tank, a tray, or a bath.
31. The system of any one of claims 27-29, wherein the first reaction chamber and the second reaction chamber comprise sensors for determining an amount of the first liquid solution or the second liquid solution in the respective reaction chamber.
32. The system of any one of claims 27-29, wherein the first and second reaction chambers comprise valves for regulating the amount of the first liquid solution or the second liquid solution in their respective reaction chambers, the valves being controlled by sensors in each reaction chamber.
33. The system of any one of claims 28, further comprising: a first rinsing chamber located between the first reaction chamber and the second reaction chamber, the first rinsing chamber containing a first rinsing solution, the first rinsing solution comprising a first solvent for rinsing the battery electrode conveyed to the first rinsing chamber by the conveying device, thereby generating a saturated first layer on the battery electrode and a first residual solution comprising the first solvent and an unreacted first reagent.
34. The system of claim 33, further comprising a first filtration device for separating the unreacted first reagent from the first solvent in the first rinse solution.
35. The system of claim 34, further comprising: A second rinsing chamber is located after the second reaction chamber, the second rinsing chamber containing a second rinsing solution, the second rinsing solution comprising a second solvent for rinsing the battery electrode transferred to the second rinsing chamber by the transfer device to produce the thin film coated on the surface of the battery electrode.
36. The system of claim 35, further comprising a second filtration device for separating unreacted second reagent from the second solvent in the second rinse solution.
37. The system of claim 36, wherein the first filtration device and the second filtration device are selected from one of the following: a separation membrane, a filtration column or a chromatography column, a chemical or electrochemical separation tank, an adsorption column, or a combination thereof.
38. The system of claim 28, wherein the lithium-ion battery anode comprises a silicon-graphite composite and the polymer material comprises aramid.
39. A system for coating an artificial solid-electrolyte interface comprising metal cones onto the surface of a lithium ion battery anode consisting of at least a silicon-graphite composite conversion material, the system comprising: A conveying device comprising a series of rollers for conveying the anode to a reaction chamber, wherein: (a) exposing the anode to a first liquid solution comprising at least a first reagent, the first reagent comprising a metal organic, to produce a layer comprising adsorbed first reagent on the anode; and (b) exposing the anode having a layer comprising an adsorbed first reagent to a second liquid solution comprising at least a second reagent comprising organic molecules, wherein the at least second reagent reacts with the adsorbed first reagent to produce an anode comprising a monolayer film coated on the surface of the anode, the monolayer film comprising metal cones produced by the reaction of the metal organic with the organic molecules.
40. The system of claim 39, wherein the metal organic comprises an organic portion and a metal, the metal comprising Al, Zn, Si, Ti, Zr, Hf, Mn and / or V, and the organic molecule comprises ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol and / or diaminodiphenyl ether.
41. A system for coating an artificial solid-electrolyte interface comprising an organic material onto the surface of a lithium ion battery anode composed of at least a silicon-graphite conversion material, the system comprising: A conveying device for conveying the anode to a reaction chamber, wherein: (a) exposing the anode to a first liquid solution comprising at least a first organic reagent to produce a layer comprising adsorbed first organic reagent on the anode; and (b) exposing the anode having a layer comprising an adsorbed first organic reagent to a second liquid solution comprising at least a second organic reagent, wherein the at least second organic reagent reacts with the adsorbed first organic reagent to produce an anode comprising a monolayer film coated on the surface of the anode, the monolayer film comprising the organic material produced by the reaction of the first organic reagent with the second organic reagent, wherein the organic material comprises a polymer material of at least one of one or more polyamides, one or more polyureas, one or more polyazimines, or one or more fluoroelastomers.
42. The system of any one of claims 27-41, further comprising a motor for driving the conveying device.
43. The system of any one of claims 27-41, further comprising a computer system for operating the conveying device.
44. A liquid phase deposition method for coating an artificial solid-electrolyte interface comprising metal cones onto the surface of a lithium ion battery anode consisting of at least a silicon-graphite composite conversion material, the method comprising: (a) providing the anode into a reaction chamber; (b) exposing the anode to a first liquid solution comprising a first reagent comprising a metal organic to produce a layer comprising adsorbed first reagent on the surface of the anode, wherein the metal organic comprises at least one of Al, Zn, Si, Ti, Zr, Hf, Mn, or V; and (c) exposing the anode having the adsorbed first reagent to a second liquid solution comprising a second reagent, the second reagent comprising an organic molecule, wherein at least the second reagent reacts with the adsorbed first reagent to produce a monolayer film coated on the surface of the anode, the monolayer film comprising the metal cones produced by the reaction of the metal organic with the organic molecule, wherein the organic molecule comprises at least one of ethylene glycol, glycerol, erythritol, xylitol, sorbitol, mannitol, butanediol, pentanediol, hydroquinone, hexanediol, lactic acid, triethanolamine, p-phenylenediamine, glycidol, caprolactone, fumaric acid, aminophenol or diaminodiphenyl ether.
45. The method of claim 44, wherein steps (a)-(c) are repeated to produce sequential growth of multiple stacked monolayers to produce a thin film coating having a total thickness between 0.5 nanometers (nm) and 100 micrometers (μm).
46. The method of claim 44 or claim 45, further comprising: rinsing the partially coated battery electrode with a first rinsing solution comprising a first solvent to produce a saturated first layer on the partially coated battery electrode and a first residual solution comprising the first solvent and unreacted first reagent; and The partially coated battery electrode is rinsed with a second rinse solution comprising a second solvent to produce a saturated monolayer film on the partially coated battery electrode and a second residual solution comprising the second solvent and unreacted second reagent.
47. The method of claim 46, further comprising: sending the first residual solution to a first filtration step to separate the unreacted first reagent from the first solvent; and The second residual rinse solution is sent to a second filtration step to separate the unreacted second reagent from the second solvent.
48. The method of claim 47, further comprising: recycling the recovered unreacted first reagent or second reagent back to the first liquid solution or the second liquid solution, respectively; and The recovered first solvent or second solvent is recycled back to the first rinse solution or second rinse solution, respectively.
49. The method of any one of claims 44-48, wherein the metal organic comprises Al and the organic molecule comprises glycerol, erythritol, xylitol, sorbitol, mannitol, or hydroquinone.
50. A liquid phase deposition method for coating an artificial solid-electrolyte interface comprising an organic material onto the surface of a lithium ion battery anode consisting of at least a silicon-graphite composite material, the method comprising: (a) providing the anode into a reaction chamber; (b) exposing the anode to a first liquid solution comprising a first organic reagent to produce a layer comprising adsorbed first organic reagent on the surface of the anode; and (c) exposing the anode having the adsorbed first organic reagent to a second liquid solution comprising a second organic reagent, wherein at least the second organic reagent reacts with the adsorbed first organic reagent to produce a monolayer film coated on the surface of the anode, the monolayer film comprising the organic material produced by the reaction of the first organic reagent with the second organic reagent, wherein the organic material comprises a polymer material of at least one of polyamide, polyurea, polyazine, or fluoroelastomer.
51. The method of claim 50, wherein steps (a)-(c) are repeated to produce sequential growth of multiple stacked monolayers to produce a thin film coating having a total thickness between 0.5 nanometers (nm) and 100 micrometers (μm).
52. The method of claim 50 or claim 51, further comprising: rinsing the partially coated battery electrode with a first rinsing solution comprising a first solvent to produce a saturated first layer on the partially coated battery electrode and a first residual solution comprising the first solvent and unreacted first reagent; and The partially coated battery electrode is rinsed with a second rinse solution comprising a second solvent to produce a saturated monolayer film on the partially coated battery electrode and a second residual solution comprising the second solvent and unreacted second reagent.
53. The method of claim 52, further comprising: sending the first residual solution to a first filtration step to separate the unreacted first reagent from the first solvent; and The second residual rinse solution is sent to a second filtration step to separate the unreacted second reagent from the second solvent.
54. The method of claim 53, further comprising: recycling the recovered unreacted first reagent or second reagent back to the first liquid solution or the second liquid solution, respectively; and The recovered first solvent or second solvent is recycled back to the first rinse solution or second rinse solution, respectively.
55. A lithium ion battery anode comprising a silicon-graphite composite conversion material, comprising: A porous microstructure coated with one or more single-layer artificial solid-electrolyte interface coatings, the coatings comprising metal cones or organic materials, wherein the organic materials comprise a polymer material of at least one of polyamide, polyurea, polyazine, or a fluoroelastomer, wherein the artificial solid-electrolyte interface is produced by the method of any one of claims 1-26 or 44-54 or the system of any one of claims 27-43.
56. The lithium ion battery anode of claim 55, wherein the elastic modulus of the thin film coating is between 0.1-100 GPa.
57. The lithium ion battery anode of claim 55, wherein the material comprises an artificial solid-electrolyte interface coating, and the volume elongation at break of the artificial solid-electrolyte interface coating is between 1% and 500%.
58. A lithium ion battery comprising the anode of any one of claims 55-57.
59. The method of claim 1, wherein the molecular weight of the organic molecule in the second reagent is between 10-10,000 Daltons.
60. The method of claim 1, wherein the active material in the lithium ion battery anode is a conversion anode material comprising at least one of Si, Sn, or Ge.
61. The method of claim 60, wherein the substrate is made of a metal such as copper, aluminum or stainless steel.
Citation Information
Patent Citations
Protective coatings for lithium anodes
US20190044151A1
Methods, systems, and compositions for the liquid-phase deposition of thin films onto the surface of battery electrodes
WO2018237083A1